Securing Healthcare Data with Advanced Asymmetric Lattice‎Galois Encryption Standard in A Decentralized Blockchain ‎Framework - Alex, K. Britto; Selvan, K. (International Journal of Basic and Applied Sciences, 2025)
Securing sensitive data is essential to protect against unauthorized access, breaches, and privacy violations. A decentralized blockchain ‎offers a robust solution by distributing data across multiple nodes, ensuring transparency, immutability, and enhanced protection, all without ‎relying on a central authority. Several clinical datasets are available, covering a wide range of healthcare-associated data. Encryption and ‎decryption, along with optimization, are techniques used to secure data by converting it into a form that is unintelligible without the precise ‎key or algorithm. These processes play a crucial role in data protection and privacy. These datasets are invaluable for numerous applications, ‎along with clinical studies, predictive analytics, system studies, and healthcare system optimization. The research presents an overall ‎approach to a safe data management case study, which uses Kaggle datasets. The approach begins with preprocessing using the Z-score ‎normalization method to ensure consistency in the dataset’s dimensions. Use a data augmentation technique to expand the data range, thereby ‎increasing the recording duration. Thereafter, an encryption scheme is implemented to maximize the security of the dataset. The encoded ‎dataset is then placed in a decentralized blockchain, which allows for the effective utilization of its infrastructure for well-organized and ‎efficient storage methods. The decryption process is facilitated by an AALGES Exchange mechanism, which securely retrieves the original ‎data. Risk simulation occurs both before and after the data reaches the storage region, allowing for an evaluation of the system’s resilience to ‎stress. This is done in the Python platform. To examine the system’s performance, it simulates the analysis in detail, specifically focusing on ‎various aspects such as encryption and decryption speed, data storage capability, and minimum computational overhead‎.